UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI KEGIATAN MONTASE DI KOBER AL-BASIR KELAS A - Hevie Setia Gunawan; Astarina Arif; Siti Halimah Sya’diyah (Jurnal Al Burhan, 2023)
This study aims to improve children's fine motor development by using montage activities at KOBER Al-Basir Sukamulya Village, Cipongkor District. The method used in this research is classroom action research, which consists of planning, implementing and reflecting which consists of 2 cycles. The results of the study showed that the development of fine motor skills in children in class A Kober Al-Basir increased. Data from research on the development of children's fine motor skills using montage activities are as follows: Cycle I, first meeting, criteria for starting to develop 26%. In the first cycle, the second meeting increased to 29.16% and in the first cycle, the third meeting increased again to 36.45%. Cycle II at the first meeting, the child's fine motor development increased to 44.79%, during Cycle II at the second meeting it increased to 61.45% and cycle II at the third meeting increased to 93.75%, which is in the very well developed criteria. Thus it can be concluded that montage activities can improve fine motor development in children.